Entre tensionamentos e diálogos: os saberes técnico-científicos e os saberes tradicionais nas práticas de aconselhamento em aleitamento materno - Bueno, Caroline de Moura (2020)
This dissertation deals with breastfeeding and is inserted in the context of Education and Development. In this thematic scope, the tension between traditional and technical knowledge is analyzed from the perspective ofthe orientations of the groups of pregnant women in a collective of mothers and nurses. In addition, the organizational aspects of these two groups are also studied and discussed. The main objective of this dissertation is to analyze such tension, as wellas the dialogues and rationalities that involve them. The basis of the theoretical subsidy used to carry out these analyzes was the concept of biopower and biopolitics, described by Michel Foucault. The author's theories are used to understand the technical-scientific and traditional knowledge and the discourses produced by public policies on breastfeeding. The methodological approach used to carry out this investigation was a descriptive research, with a qualitative approach, with semi-structured interviews being conducted in two groups with individuals from the city of Pato Branco, Paraná. The main analyzes produced by the study are divided into two categories: the organizational / institutional aspects in the counseling process from a collective and a public organization and the tension between technical and scientific knowledge and traditional knowledge. The first category refers to the organizational processes of maternal counseling and the main characteristics are the flexibility and autonomy in the collective meetings in view of the instrumental rationality of the groups of pregnant women in the health units. In the second category, the balance that occurs between traditional knowledge, supported by experiences, and technical-scientific knowledge in the collective and the dichotomy existing in the nurses' discourse between these two types of knowledge stands out. It is observed in the two groups analyzed that motherhood goes through these practices in the sense that breastfeeding counseling occurs supported by these experiences. Through Foucault's reflections, the bias of social control and the legitimation of truth discourses were discussed. In view of the two perspectives, it is possible to emphasize the diversity of disciplinary techniques in the Breastfeeding Manuals, as it values instrumental knowledge in view of the plurality of ideas from the collective of mothers. However, it is also important to emphasize that the tension lies in this overlap, of health and care, and that the participants of the present study demonstrate the power relations in the reproduction of these technical-scientific discourses without denying the importance of the experiences in breastfeeding counseling. At the center of this clash of perceived knowledge and powers, there is a need for articulation between public spheres and non-conventional organizations to understand the actions in the context of maternal counseling as a socio-cultural practice and to value the plurality of knowledge existing in this theme.